Effect of sodium on transport of weak electrolytes across rat jejunum in vitro. - Jackson, M J (1984)
The effects of ion substitution and inhibitors on the transport of two representative weak electrolytes, benzoic acid and amphetamine, across short-circuited rat jejunum in vitro have been studied. The spontaneous asymmetries in the transport of the weak electrolytes were not dependent on the presence of either bicarbonate or chloride in the incubation medium. Net transport of the weak electrolytes was abolished when choline was substituted for sodium in the fluid bathing the mucosal surface of the tissue, but weak electrolyte transport was independent of the presence of sodium on the serosal side. Weak electrolyte transport was inhibited by ouabain and by orthovanadate. The effect of ouabain was abolished when potassium was substituted for sodium in the serosal fluid, and the effect of orthovanadate was potentiated in this condition. It was shown that the ability of the intestinal epithelium to discriminate between the ionized and non-ionized forms of weak electrolytes was not altered when choline was substituted for sodium in the incubation medium, indicating that the effect of sodium was associated with the driving force for weak electrolyte transport. Weak electrolyte transport was not abolished by raising the serosal potassium concentration, suggesting that the transport process was directly related with the function of the sodium pump, rather than correlated with gradients of electrical or chemical potential established as a consequence of pump activity.